Vitamin K2 biosynthetic enzyme, UBIAD1 is essential for embryonic development of mice. - Kimie Nakagawa (Public Library of Science (PLoS), 2014)
UbiA prenyltransferase domain containing 1 (UBIAD1) is a novel vitamin K2 biosynthetic enzyme screened and identified from the human genome database. UBIAD1 has recently been shown to catalyse the biosynthesis of Coenzyme Q10 (CoQ10) in zebrafish and human cells. To investigate the function of UBIAD1 in vivo, we attempted to generate mice lacking Ubiad1, a homolog of human UBIAD1, by gene targeting. Ubiad1-deficient (Ubiad1(-/-)) mouse embryos failed to survive beyond embryonic day 7.5, exhibiting small-sized body and gastrulation arrest. Ubiad1(-/-) embryonic stem (ES) cells failed to synthesize vitamin K2 but were able to synthesize CoQ9, similar to wild-type ES cells. Ubiad1(+/-) mice developed normally, exhibiting normal growth and fertility. Vitamin K2 tissue levels and synthesis activity were approximately half of those in the wild-type, whereas CoQ9 tissue levels and synthesis activity were similar to those in the wild-type. Similarly, UBIAD1 expression and vitamin K2 synthesis activity of mouse embryonic fibroblasts prepared from Ubiad1(+/-) E15.5 embryos were approximately half of those in the wild-type, whereas CoQ9 levels and synthesis activity were similar to those in the wild-type. Ubiad1(-/-) mouse embryos failed to be rescued, but their embryonic lifespans were extended to term by oral administration of MK-4 or CoQ10 to pregnant Ubiad1(+/-) mice. These results suggest that UBIAD1 is responsible for vitamin K2 synthesis but may not be responsible for CoQ9 synthesis in mice. We propose that UBIAD1 plays a pivotal role in embryonic development by synthesizing vitamin K2, but may have additional functions beyond the biosynthesis of vitamin K2.